Sosialisasi Desain Visual Brand Identity Friendly Bagi Usaha Masyarakat Kecil dan Menengah (UMKM) - Riandana Afira; Irdam; Widia Marta (Universitas Putra Indonesia YPTK Padang, 2021)
Small and Medium Enterprises (MSMEs) Hobby Wood Padang is one of the wood craftsman communities in the city of Padang. The hobby of Kayu Padang has produced many works and creativity from wood raw materials. The rapid growth and competition in the world of technology and information in Indonesia, especially in the city of Padang, production competition is getting higher and we need to innovate even more. In order to compete with Padang wood hobby competitors, it is necessary to have a solid and consistent visual brand identity to the public so that the company can be more easily recognized by the public's mind. The visual brand identity design is carried out by elevating the company's image that is exclusive, unique, Asian-style, especially Indonesia-Padang with a friendly and warm family culture. The problem here is how to make branding that can be promoted nationally and internationally by utilizing Visual Brand Identity. With attractive branding, it will help every business owner to be more different and stand out from the competitors. This outreach program aims to provide understanding to the members of the Kayu Padang Hobby crafts community about attractive branding for promotion and building the image of the community and is expected to improve the quality of the Kayu Padang Hobi crafts community in making branding more attractive. Besides that, a continuous program is also needed so that the stages of material and socialization provided can be carried out perfectly and in accordance with the expected goals.